Warum lieferte Judas Jesus aus ? - Ehling, Kay (Biblische Notizen, 2008)
Judas handed Jesus over to the Jewish authorities not because he was disappointed in Jesus’s unfulfilled messianity. To the contrary, because Judas appears to have had traditional beliefs and was a defender of the Torah he was concerned with Jesus’ messianic claim during his last days in Jerusalem and regarded it as too far-reaching. Judas feared Jesus’s questioning of the Torah and this motivated him to turn to the members of the Sanhedrin for the arrest of Jesus.